Factors Associated with Disaster Response Competency of Nursing Students in Graduation Years (Medico Legal Update, 2021)
Background: This study was conducted to provide the basis for the disaster nursing curriculum throughgrasping the degree of disaster preparedness attitude and disaster response competency of the senior nursingstudent.Method: Data was collected through a questionnaire for senior nursing students from five universities inSouth Korea. A total of 168 data were analyzed through the IBM SPSS 25.0 program.Finding: Disaster response competency were most strongly predicted by “satisfied” major satisfaction,followed by “average” major satisfaction, “realization of good deeds” motivation, “yes” experience ofdisaster education. The explanatory power by these variables was 19.7%.Conclusion: The results of this study suggested that the experience of disaster education is importantto improve the disaster response competency of nursing students. In preparation for disasters that areunpredictable and lead to serious resource shortages, nursing colleges will have to make efforts to providesufficient education and training.